2022
DOI: 10.1182/bloodadvances.2021004915
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory viruses in hematopoietic cell transplant candidates: impact of preexisting lower tract disease on outcomes

Abstract: Pretransplant respiratory virus infections (RVIs) have been shown to negatively impact hematopoietic cell transplantation (HCT) outcomes. The impact of and need for delay of HCT for pretransplant infection with human rhinovirus (HRV) or endemic human coronavirus (HCoV) (229E, OC43, NL63, and HKU1) remains controversial. We analyzed the impact of symptomatic RVI within <90 days prior to HCT on overall mortality, posttransplant lower respiratory tract disease (LRD), and days alive and out of hospital (DAO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Finally, it is important to note that mAbs are currently available for only two viruses, RSV and SARS-CoV-2. There is a significant unmet need for mAbs against other respiratory viruses like influenza, human metapneumovirus, and the parainfluenza viruses that afflict immunocompromised patients and cause significant morbidity and mortality [4 ▪ ,44 ▪ ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is important to note that mAbs are currently available for only two viruses, RSV and SARS-CoV-2. There is a significant unmet need for mAbs against other respiratory viruses like influenza, human metapneumovirus, and the parainfluenza viruses that afflict immunocompromised patients and cause significant morbidity and mortality [4 ▪ ,44 ▪ ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunocompromised patients have increased susceptibility to severe complications due to respiratory viral infections, including death. For example, hematopoietic stem cell transplant (HCT) recipients represent a subgroup of immunocompromised patients that are extremely vulnerable to respiratory viruses due to loss of immunity after conditioning chemotherapy [1 ▪ –4 ▪ ]. This is modeled in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that age and a shorter time from transplantation to COVID-19 are associated with poor outcomes 1 , 4 , 27 . For other respiratory viruses, the presence of LRTI and myeloablative conditioning are associated with increased risk of post-HCT complications 28 . In a recent systematic review, a higher performance status was associated with decreased mortality in HCT recipients acquiring COVID-19 at all stages following transplant (HR=0.83, 95%CI 0.74-0.93, p=0.001) 29 .Based on our expert opinion and clinical experience in management of COVID-19 among this population, we provide a summary of recommendations on evaluation of HCT and cellular therapy candidates in table 1 .…”
Section: Pre-transplant Hct and Cellular Therapy Candidates And Donor...mentioning
confidence: 99%
“…Since that time, SARS-CoV-2 has been responsible for over 6 million deaths from Coronavirus Disease 2019 (COVID-19) 1 . Respiratory viral infections, in general, place an outsized burden on immunocompromised hosts, and increase the mortality 2 . Therefore, there was significant concern from the outset of the pandemic that SARS-CoV-2 infection would similarly impact immunocompromised patients disproportionately.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, mortality was over twofold higher among immunocompromised patients with influenza pneumonia. Other respiratory viruses also affect the immunocompromised; a recent retrospective cohort study of 1643 hematopoietic cell transplant patients found increased mortality in allogeneic recipients infected with human rhinovirus (HRV) and adenovirus lower respiratory infections 2 . Finally, human herpesvirus-6 (HHV-6) and cytomegalovirus (CMV) have long been associated with increased mortality amongst hematopoietic cell transplant recipients 8 .…”
Section: Introductionmentioning
confidence: 99%